Ternary positive electrode material and preparation method thereof
Through one-step precipitation method, a variety of fast-ion conductor precursors are deposited on the surface of the ternary positive electrode material, and the polycrystalline material is prepared by combining lithium salt calcination, which solves the magnification and cyclic performance of high-nickel materials, and significantly improves the stability of the material performance and performance.
Patent Information
- Application Number
- CN202411379348.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-30
Smart Images

Figure BDA0005069509530000051 
Figure HDA0005069509540000011 
Figure HDA0005069509540000012
Abstract
Description
Technical Field
[0001] The invention relates to a ternary positive electrode material and a preparation method thereof, belonging to the technical field of positive electrode materials for lithium ion batteries. Background Art
[0002] Ternary lithium-ion batteries are widely used in the field of power vehicles due to their high energy density. In order to further improve the energy density, ternary cathode materials are gradually becoming high-nickel. The increase in nickel content can improve the energy density of ternary materials, but it also brings many defects such as poor material stability and reduced safety, which deteriorates the material's cycle and rate performance. In order to improve the performance of high-nickel cathode materials, researchers have proposed various methods, mainly including optimizing the synthesis process, doping and coating.
[0003] Coating is a common and effective modification method. Common coating materials include Al2O3, ZrO2, MgO2 and H2WO4, among which a small amount of coating of materials such as Al2O3, ZrO2, H2WO4 can react with residual lithium on the surface of the material to generate fast ion conductor materials, which can improve the rate performance of the material. At the same time, the generated fast ion conductor materials and oxides can effectively prevent HF corrosion, isolate the electrolyte from the positive electrode reaction, and improve the material cycle performance. At present, most coatings are dry coatings, which cannot be coated uniformly. Based on this, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a ternary positive electrode material. A surface-modified ternary precursor is prepared by a one-step precipitation method, and multiple fast ion conductor precursors are deposited simultaneously on the surface of the ternary precursor. The polycrystalline positive electrode material obtained by mixed lithium sintering of the modified ternary precursor has excellent rate and cycle performance.
[0005] The method for preparing the ternary positive electrode material provided by the present invention comprises the following steps:
[0006] S1, preparing aqueous solutions of water-soluble metal hydrochloride salt a, mixed salt b and complexing agent, which are respectively recorded as solution A, solution B and solution C;
[0007] S2, adding the complexing agent, the ternary precursor and water into a reaction kettle, stirring to obtain slurry D;
[0008] S3, under stirring, simultaneously passing the solution A, the solution B and the solution C into the slurry D for surface deposition to obtain a surface-modified ternary precursor;
[0009] S4. The surface modified ternary precursor is mixed with lithium salt and calcined to obtain a ternary positive electrode material.
[0010] In the preparation method of the present invention, the metal hydrochloride salt a is MoO4 2-WO4 2- One or more of potassium salt, sodium salt and water-soluble ammonium salt;
[0011] The mixed salt b includes a main component c and a doping and modification component d;
[0012] The main component c includes at least one of aluminum salt and zirconium salt, and the doping modification component d includes at least one of lanthanum salt and yttrium salt;
[0013] The complexing agent is one of potassium salt and sodium salt of citric acid and tartaric acid.
[0014] In the preparation method of the present invention, the aluminum salt, the zirconium salt, the lanthanum salt and the yttrium salt are all sulfates or nitrates of the corresponding metals.
[0015] In the preparation method of the present invention, in the mixed salt b, the ratio of the total metal molar amount contained in the main component c to the total metal molar amount contained in the doping modification component d is 1:0.05-0.1.
[0016] In the preparation method of the present invention, in step S1, the total solute concentration in solution A is 0.1-0.5 mol / L, the total solute concentration in solution B is 0.1-1 mol / L, and the total solute concentration in solution C is 0.5-5 mol / L.
[0017] In the preparation method of the present invention, in step S2, the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.3≤x<1, 0 <y≤0.3,x+y<1;
[0018] In the slurry D, the concentration of the complexing agent is 0.02-0.05 mol / L, and the solid concentration of the ternary precursor is 300-600 g / L.
[0019] In the preparation method of the present invention, in step S3, the solution A, the solution B and the solution C are all introduced into the slurry D through a flow pump, and the flow rates of the solution A and the solution B are controlled so that the metal acid radicals introduced into the slurry D can be completely precipitated by the metal ions in the solution B per unit time; the flow rate of the solution C is controlled so that the concentration of the complexing agent during the reaction is kept consistent with the initial concentration of the complexing agent in the slurry D;
[0020] The conditions for the surface deposition are as follows:
[0021] The reaction atmosphere is an inert atmosphere, the reaction temperature is 50-70°C, and the stirring speed is 500-700r / min;
[0022] The mass ratio of the metal acid salt a to the ternary precursor introduced into the slurry D is 0.005 to 0.01:1, such as 0.005:1 or 0.01:1.
[0023] In the preparation method of the present invention, step S3 also includes the step of washing the surface modified ternary precursor with deionized water until the alkali metal content of the material is less than 100 ppm, and then drying under the following conditions: temperature of 80-120° C., time of 5-12 hours.
[0024] In the preparation method of the present invention, in step S4, the lithium salt is one of lithium carbonate and lithium hydroxide;
[0025] The molar ratio of lithium element in the lithium salt to total metal ions in the surface modified ternary precursor is 1:1.03-1.05;
[0026] The calcination temperature is 800-850° C., the calcination time is 10-20 hours, and the sintering atmosphere is air atmosphere or oxygen atmosphere.
[0027] The ternary positive electrode material prepared by the method of the present invention also falls within the protection scope of the present invention.
[0028] The present invention utilizes metal acid radical ions and metal ions to carry out precipitation reaction, and through a simple one-step precipitation method, realizes the simultaneous deposition of multiple fast ion conductor precursors (such as aluminum tungstate, zirconium tungstate, zirconium molybdate, etc.) on the surface of a ternary precursor; after the fast ion conductor precursor is mixed with lithium and sintered, a multi-component fast ion conductor (such as lithium tungstate, lithium molybdate, lithium aluminate, lithium zirconate, etc.) can be generated, which can significantly reduce the interfacial lithium ion transmission energy barrier of the positive electrode material, thereby improving the material rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the unmodified ternary precursor.
[0030] Figure 2 This is the SEM image of the surface-modified ternary precursor obtained in step (4) of Example 5 of the present invention. DETAILED DESCRIPTION
[0031] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0032] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0033] Embodiment 1,
[0034] (1) Add metal acid salt sodium tungstate, aluminum sulfate and lanthanum nitrate mixed salt and sodium citrate into deionized water respectively, and dissolve to obtain solutions A, B and C with molar concentrations of 0.1 mol / L, 0.1 mol / L (total molar concentration of aluminum sulfate and lanthanum nitrate) and 0.5 mol / L respectively; wherein the molar concentration ratio of aluminum sulfate to lanthanum nitrate in solution B is 1:0.05;
[0035] (2) Sodium citrate, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and deionized water were added to the reactor and stirred to obtain a sodium citrate molar concentration of 0.02 mol / L and Ni 0.8 Co 0.1 Mn 0.1 Slurry D with a (OH)2 solid content of 300 g / L;
[0036] (3) In a nitrogen atmosphere, at a speed of 500 r / min and a reaction temperature of 50°C, solution A, solution B and solution C are simultaneously introduced into slurry D for surface deposition reaction. By controlling the flow rates of solutions A and B, the metal acid radicals introduced into slurry D can be completely precipitated by the metal ions in solution B according to the stoichiometric ratio per unit time. By controlling the flow rate of solution C, the concentration of the complexing agent is maintained at 0.02 mol / L during the reaction. When the mass of sodium tungstate introduced reaches Ni 0.8 Co 0.1 Mn 0.1 When the mass of (OH)2 reaches 0.5%, the feed is stopped and the reaction is finished.
[0037] (4) The obtained slurry was filtered, washed with deionized water, and dried at 80° C. for 12 h to obtain a surface-modified ternary precursor, and the sodium ion content of the precursor was measured to be 93 ppm;
[0038] (5) The surface modified ternary precursor is mixed with lithium carbonate salt, and calcined at 800° C. for 10 h in an air atmosphere to obtain a ternary positive electrode material, wherein the molar ratio of lithium element to the total metal elements (nickel, cobalt, manganese, tungsten, lanthanum, aluminum) in the modified ternary precursor is 1:1.03.
[0039] Embodiment 2,
[0040] (1) adding metal acid salt potassium molybdate, zirconium sulfate yttrium nitrate mixed salt and potassium tartrate into deionized water respectively, dissolving to obtain solutions A, B and C with molar concentrations of 0.5 mol / L, 1 mol / L (total molar concentration of zirconium sulfate and yttrium nitrate) and 5 mol / L respectively; wherein the molar concentration ratio of zirconium sulfate to yttrium nitrate in solution B is 1:0.1;
[0041] (2) Potassium tartrate, Ni 0.8 Co 0.1Mn 0.1 (OH)2 and deionized water were added to the reactor and stirred to obtain a potassium tartrate molar concentration of 0.05 mol / L and Ni 0.8 Co 0.1 Mn 0.1 Slurry D with a (OH)2 solid content of 600 g / L;
[0042] (3) In a nitrogen atmosphere, at a speed of 700 r / min and a reaction temperature of 70°C, solution A, solution B and solution C are simultaneously introduced into slurry D for surface deposition reaction. By controlling the flow rates of solutions A and B, the metal acid radicals introduced into slurry D can be completely precipitated by the metal ions in solution B according to the stoichiometric ratio per unit time. By controlling the flow rate of solution C, the concentration of the complexing agent is maintained at 0.05 mol / L during the reaction. When the mass of sodium tungstate introduced reaches Ni 0.8 Co 0.1 Mn 0.1 When the mass of (OH)2 is 1%, the feed is stopped and the reaction is finished.
[0043] (4) The obtained slurry was filtered, washed with deionized water, and dried at 120° C. for 5 h to obtain a surface-modified ternary precursor, and the potassium ion content of the precursor was measured to be 87 ppm;
[0044] (5) The surface-modified ternary precursor is mixed with lithium hydroxide and calcined at 850° C. for 10 h in an oxygen atmosphere to obtain a ternary positive electrode material, wherein the molar ratio of lithium element to the total metal elements (nickel, cobalt, manganese, tungsten, yttrium, zirconium) in the modified ternary precursor is 1:1.05.
[0045] Embodiment 3,
[0046] (1) Add metal acid salt sodium tungstate, aluminum nitrate lanthanum nitrate mixed salt and potassium tartrate into deionized water respectively, dissolve to obtain solutions A, B and C with molar concentrations of 0.5 mol / L, 0.2 mol / L (total molar concentration of aluminum nitrate and lanthanum nitrate) and 5 mol / L respectively; wherein the molar concentration ratio of aluminum nitrate to lanthanum nitrate in solution B is 1:0.08;
[0047] (2) Sodium tartrate, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and deionized water were added to the reactor and stirred to obtain a sodium potassium tartrate molar concentration of 0.03 mol / L and Ni 0.8 Co 0.1 Mn 0.1 Slurry D with a (OH)2 solid content of 600 g / L;
[0048] (3) In a nitrogen atmosphere, at a speed of 700 r / min and a reaction temperature of 70°C, solution A, solution B and solution C are simultaneously introduced into slurry D for surface deposition reaction. By controlling the flow rates of solutions A and B, the metal acid radicals introduced into slurry D can be completely precipitated by the metal ions in solution B according to the stoichiometric ratio per unit time. By controlling the flow rate of solution C, the concentration of the complexing agent is maintained at 0.03 mol / L during the reaction. When the mass of sodium tungstate introduced reaches Ni 0.8 Co 0.1 Mn 0.1 When the mass of (OH)2 is 1%, the feed is stopped and the reaction is finished.
[0049] (4) The obtained slurry was filtered, washed with deionized water, and dried at 120° C. for 5 h to obtain a surface-modified ternary precursor, and the sodium ion content of the precursor was measured to be 95 ppm;
[0050] (5) The surface-modified ternary precursor is mixed with lithium carbonate and calcined at 830° C. for 15 h in an oxygen atmosphere to obtain a ternary positive electrode material, wherein the molar ratio of lithium element to the total metal elements (nickel, cobalt, manganese, tungsten, lanthanum, and aluminum) in the modified ternary precursor is 1:1.04.
[0051] Embodiment 4,
[0052] The difference between Example 4 and Example 3 is that in step (2), Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 solid content is 500g / L.
[0053] Embodiment 5,
[0054] The difference between Example 5 and Example 4 is that in step (3), the mass of sodium tungstate introduced is Ni 0.8 Co 0.1 Mn 0.1 (OH)2 mass 0.8%.
[0055] from Figure 1 , Figure 2 It can be seen that after the coprecipitation modification, there is obviously an additional layer of covering on the surface of the particles, indicating that the coprecipitation product is successfully deposited on the surface of the particles.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 5 is that there is no doped modified component, the aluminum nitrate and lanthanum nitrate mixed salt is replaced by single aluminum nitrate, and the other parameters and steps remain unchanged;
[0058] Comparative Example 2
[0059] Directly transfer unmodified Ni 0.8 Co0.1 Mn 0.1 (OH)2 was mixed with lithium carbonate and calcined at 830°C for 15h in an oxygen atmosphere to obtain a ternary positive electrode material, in which the molar ratio of lithium element to the total metal elements (nickel, cobalt, manganese) in the modified ternary precursor was 1:1.04.
[0060] Comparative Example 3
[0061] The difference between Comparative Example 3 and Example 5 is that in step (1), the molar concentration ratio of aluminum nitrate to lanthanum nitrate in solution B is 1:0.01.
[0062] Comparative Example 4
[0063] The difference between Comparative Example 4 and Example 5 is that in step (1), the molar concentration ratio of aluminum nitrate to lanthanum nitrate in solution B is 1:0.15.
[0064] Characterization of electrochemical properties: The positive electrode materials before and after modification were made into button batteries, in which the active material: conductive agent: binder = 90:5:5 (mass ratio), the conductive agent is Super P, the binder is PVDF, the electrolyte is 1M LiPF6 dissolved in a mixed solvent of EC, DEC and DMC (volume ratio of 1:1:1), and the test voltage range is 2.8-4.25V; the first round of charge and discharge was tested at 0.1C / 0.1C, and the cycle retention rate was measured under 1C / 1C charge and discharge conditions.
[0065] Table 1 Electrical performance data of each example sample
[0066]
[0067] From the charge and discharge capacity data of Examples 1-5 and Comparative Example 1, it can be seen that the surface modification of the precursor has little effect on the charge and discharge capacity of the positive electrode material under 0.1C conditions, but has a greater impact on the discharge capacity of the material under high rate conditions, significantly improving the capacity of the material under 1C and 2C discharge rates. This is because the coating layer deposited on the surface of the precursor can generate a multi-component fast ion conductor (such as tungsten / lithium aluminate, molybdenum / lithium zirconium, etc.) after mixed lithium sintering, which can significantly reduce the interfacial lithium ion transmission energy barrier of the positive electrode material, thereby improving the material rate performance. At the same time, the surface fast ion conductor component weakens the reaction between the positive electrode material and the electrolyte, and also improves the cycle performance of the material.
[0068] From the data of Example 5 and Comparative Example 2, it can be seen that the doping modification component plays an important role in improving the rate performance of the material, and can further improve the rate performance of the positive electrode material. At the same time, the presence or absence of the doping component has little effect on the material cycle performance.
[0069] It can be seen from the data of Comparative Examples 3, 4, Example 5, and Comparative Examples 2 and 1 that coating can significantly improve the cycle performance of the material, but when the content of doped modified components in the coating layer is too much or too little, the coating layer will significantly weaken the improvement in the rate performance of the material.
Claims
1. A method for preparing a ternary positive electrode material, comprising the following steps: S1, preparing aqueous solutions of water-soluble metal hydrochloride salt a, mixed salt b and complexing agent, which are respectively recorded as solution A, solution B and solution C; S2, adding the complexing agent, the ternary precursor and water into a reaction kettle, stirring to obtain slurry D; S3, under stirring, simultaneously passing the solution A, the solution B and the solution C into the slurry D for surface deposition to obtain a surface-modified ternary precursor; S4. The surface modified ternary precursor is mixed with lithium salt and calcined to obtain a ternary positive electrode material.
2. The preparation method according to claim 1, characterized in that: The metal hydrochloride salt a is MoO4 2- WO4 2- One or more of potassium salt, sodium salt and water-soluble ammonium salt; The mixed salt b includes a main component c and a doping and modification component d; The main component c includes at least one of aluminum salt and zirconium salt, and the doping modification component d includes at least one of lanthanum salt and yttrium salt; The complexing agent is one of potassium salt and sodium salt of citric acid and tartaric acid.
3. The preparation method according to claim 2, characterized in that: The aluminum salt, the zirconium salt, the lanthanum salt and the yttrium salt are all sulfates or nitrates of corresponding metals.
4. The preparation method according to claim 2 or 3, characterized in that: In the mixed salt b, the ratio of the total molar amount of metals contained in the main component c to the total molar amount of metals contained in the doping and modification component d is 1:0.05-0.
1.
5. The preparation method according to claim 2 or 3, characterized in that: In step S1, the total solute concentration in solution A is 0.1-0.5 mol / L, the total solute concentration in solution B is 0.1-1 mol / L, and the total solute concentration in solution C is 0.5-5 mol / L.
6. The preparation method according to claim 2 or 3, characterized in that: In step S2, the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.3≤x<1, 0 <y≤0.3,x+y<1; In the slurry D, the concentration of the complexing agent is 0.02-0.05 mol / L, and the solid concentration of the ternary precursor is 300-600 g / L.
7. The preparation method according to claim 2 or 3, characterized in that: In step S3, the solution A, the solution B and the solution C are all introduced into the slurry D through a flow pump, and the flow rates of the solution A and the solution B are controlled so that the metal acid radicals introduced into the slurry D can be completely precipitated by the metal ions in the solution B per unit time; the flow rate of the solution C is controlled so that the concentration of the complexing agent during the reaction is consistent with the initial concentration of the complexing agent in the slurry D; The conditions for the surface deposition are as follows: The reaction atmosphere is an inert atmosphere, the reaction temperature is 50-70°C, and the stirring speed is 500-700r / min; The mass ratio of the metal acid salt a to the ternary precursor introduced into the slurry D is 0.005-0.01:
1.
8. The preparation method according to claim 2 or 3, characterized in that: Step S3 also includes the step of washing the surface modified ternary precursor with deionized water until the alkali metal content of the material is less than 100 ppm, and then drying under the following conditions: temperature of 80-120° C., time of 5-12 hours.
9. The preparation method according to claim 2 or 3, characterized in that: In step S4, the lithium salt is one of lithium carbonate and lithium hydroxide; The molar ratio of lithium element in the lithium salt to total metal ions in the surface modified ternary precursor is 1:1.03-1.05; The calcination temperature is 800-850° C., the calcination time is 10-20 hours, and the sintering atmosphere is air atmosphere or oxygen atmosphere.
10. The ternary positive electrode material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Coated and modified LiNi<0.8>Co<0.1>Mn<0.1>O<2> ternary positive electrode material and preparation method and battery thereof
CN109768248A
Preparation method of lithium lanthanum zirconate coated ternary positive electrode material
CN114068894A
Preparation method of NASICON type fast ion conductor Li1+NYNZr2-N (PO4) 3 coated single crystal high-nickel ternary composite material
CN116632205A
Method for preparing fast ion conductor coated ternary positive electrode material through low-temperature sintering, obtained material and application
CN116741956A
Modified ternary positive electrode material, preparation method thereof and lithium ion battery
CN118352509A